2020
DOI: 10.33380/2305-2066-2020-9-2-33-44
|View full text |Cite
|
Sign up to set email alerts
|

The Prospect of Creating Medicines Based on Selenium Nanoparticles (Review)

Abstract: Introduction. The prospects of using nanoparticles in the production of medicines are widely discussed in the literature. In 2018 alone, the quantity of registration certificates issued by national regulators for medicines that use nanoparticles in one form or another is around forty. Most of them are medicines based on liposomes, polymers, iron oxides, micelles. So far, no registration certificates have been issued for selenium nanoparticles. One of the reasons for this situation in this area, from our point … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…In [ 1 5 ], the authors point out that the surgical intervention is performed by separating the components by posterior opening or using an endoscopic approach, which shows good results and eliminates the risk of recurrences and blood loss, but this tactic involves massive surgical intervention and has contraindications for certain categories of patients, for example, the geriatrics. The retro rectus method with the polypropylene mesh, proposed in [ 5 18 19 ] for restoring the midline of the anterior abdominal wall with IVH, according to the results presented by the authors, is safe and characterized by minimal complications and recurrences for medium-sized hernias (6–13%). For the recovery of large sizes hernias, the method is recognized as the procedure of choice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [ 1 5 ], the authors point out that the surgical intervention is performed by separating the components by posterior opening or using an endoscopic approach, which shows good results and eliminates the risk of recurrences and blood loss, but this tactic involves massive surgical intervention and has contraindications for certain categories of patients, for example, the geriatrics. The retro rectus method with the polypropylene mesh, proposed in [ 5 18 19 ] for restoring the midline of the anterior abdominal wall with IVH, according to the results presented by the authors, is safe and characterized by minimal complications and recurrences for medium-sized hernias (6–13%). For the recovery of large sizes hernias, the method is recognized as the procedure of choice.…”
Section: Discussionmentioning
confidence: 99%
“…The structure of the wound complications mainly indicates: suppuration, the wound edges divergence, seroma, inflammatory infiltrate, long-term lymphorrhea, ligature fistulas, and wound edges necrosis [ 14 15 16 17 ]. The “new” complications, those caused exclusively by synthetic mesh prostheses, are the prosthesis migrating into the lumen of the hollow organ; intestinal fistula induced by trauma to the intestinal wall; prosthetic cyst; adhesive intestinal obstruction (seen when the intestine adheres to the prosthesis); and mesh rupture with the recurrent hernia or infringement of the hollow organs [ 14 18 19 ]. However, data collected about these complications are contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…We have found just a few publications dedicated to long-term influence of professional bleaching on individual oral hygiene. For example, Skorinova et al [ 28 ] in 2020 estimated results of home dental bleaching and found no significant differences in hygienic index in the estimated and control groups 6 months after the procedure. Fernández et al [ 29 ] were estimating psycho-emotional status of patients for 9 months after professional bleaching and, on the contrary, noted that bleaching had good influence on esthetic self-estimation of smile and motivated patients in maintaining health of oral cavity.…”
Section: Discussionmentioning
confidence: 99%
“…The main symptoms are severe pain (absent in 20% of cases) in the abdomen [4], [10], nausea (93%), vomiting (80%), diarrhea (48%), and general weakness [11]. AMI can be unclear or proceed under the guise of other diseases of the abdominal organs so the diagnosis of this pathology is very difficult [12]. The long-term pain without obvious signs of surgical pathology is a reason to suspect mesenteric vessels thrombosis [13].…”
Section: One Of the Main Reasons For The Development Of Mesenteric Embolism Is Diseases With A Risk Ofmentioning
confidence: 99%